Evaluation and Differential Diagnosis of a Genetic Marked Brucella Vaccine A19ΔvirB12 for Cattle - Yang, Jianghua; He, Chuanyu; Zhang, Huan; Liu, Mengzhi; Zhao, Hailong; Ren, Lisong; Wu, Dongling; Du, Fangyuan; Liu, Baoshan; Han, Xiaohu; He, Sun; Chen, Zeliang (Frontiers in Immunology, 2021)
Brucella abortus is an important zoonotic pathogen that causes severe economic loss to husbandry and poses a threat to human health. The B. abortus A19 live vaccine has been extensively used to prevent bovine brucellosis in China. However, it is difficult to distinguish the serological response induced by A19 from that induced by natural infection. In this study, a novel genetically marked vaccine, A19ΔvirB12, was generated and evaluated. The results indicated that A19ΔvirB12 was able to provide effective protection against B. abortus 2308 (S2308) challenge in mice. Furthermore, the safety and protective efficacy of A19ΔvirB12 have been confirmed in natural host cattle. Additionally, the VirB12 protein allowed for serological differentiation between the S2308 challenge/natural infection and A19ΔvirB12 vaccination. However, previous studies have found that the accuracy of the serological detection based on VirB12 needs to be improved. Therefore, we attempted to identify potential supplementary antigens with differential diagnostic functions by combining label-free quantitative proteomics and protein chip technology. Twenty-six proteins identified only in S2308 were screened; among them, five proteins were considered as potential supplementary antigens. Thus, the accuracy of the differential diagnosis between A19ΔvirB12 immunization and field infection may be improved through multi-antigen detection. In addition, we explored the possible attenuation factors of Brucella vaccine strain. Nine virulence factors were downregulated in A19ΔvirB12. The downregulation pathways of A19ΔvirB12 were significantly enriched in quorum sensing, ATP-binding cassette transporter, and metabolism. Several proteins related to cell division were significantly downregulated, while some proteins involved in transcription were upregulated in S2308. In conclusion, our results contribute to the control and eradication of brucellosis and provide insights into the mechanisms underlying the attenuation of A19ΔvirB12.